Peran Profitabilitas dalam Memediasi Hubungan Struktur Modal dengan Return Saham dan Peran Nilai Tukar dalam Memoderasi Hubungan Profitabilitas dengan Return Saham - Dien Rizka Aulia; Bambang Mahmudi; Ana Susi Mulyani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the role of profitability in mediating the relationship between capital structure and stock returns, as well as the role of exchange rates in moderating the relationship between profitability and stock returns. This quantitative research employs a saturated sampling technique with a total of 36 companies, using data analysis methods including t-tests, step causal mediation tests, and Moderated Regression Analysis (MRA) with SPSS 27. The results show that capital structure has a negative effect on stock returns and also negatively affects profitability, while profitability has a positive effect on stock returns. Profitability is proven to mediate the relationship between capital structure and stock returns, whereas exchange rates do not moderate the relationship between profitability and stock returns. Theoretically, this research enriches the literature on the relationship between capital structure, profitability, and exchange rates with stock returns, particularly in the consumer goods industry sector. The practical implication of this study is to provide insights for companies in the consumer goods sector to focus on cost control strategies and profit efficiency improvements in order to enhance stock returns. The limitation of this study lies in its focus only on internal factors such as capital structure and profitability; therefore, further research is needed to explore additional factors to obtain a more comprehensive understanding.